Answer:
a) True
<em> </em><em></em>
Step-by-step explanation:
<u><em>Step(i):-</em></u>
<em>Given that the definite integration</em>
<em> </em><em></em>
<em>we know that the trigonometric formula</em>
<em> sin²∝+cos²∝ = 1</em>
<em> cos²∝ = 1-sin²∝</em>
<u><em>step(ii):-</em></u>
<em>Now the integration</em>
<em> </em><em></em>
<em> = </em><em></em>
<em>Now, Integrating </em>
<em> </em><em></em>
<em> = sin π - sin 0</em>
<em> = 0-0</em>
<em> = 0</em>
<u><em>Final answer:-</em></u>
<em> </em><em></em>
<em></em>
<em></em>